2019
DOI: 10.1021/acs.analchem.9b01268
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Immobilization of β2-AR Using O6-Benzylguanine Derivative-Functionalized Supporter for High-Throughput Receptor-Targeting Lead Discovery

Abstract: The past decade has witnessed the great promise of strategies for ligand discovery based on surface-immobilized GPCRs. We present here a method for preparation of immobilized GPCRs. Key features include covalent immobilization with high specificity and robust application in drugreceptor interaction analysis and ligand screening. In our example assay using beta 2 -adrenergic receptor (β 2 -AR), the human DNA repair protein O 6alkylguanine-DNA alkyltransferase (hAGT) fusion receptor expressed in Escherichia coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 41 publications
(59 reference statements)
0
17
0
Order By: Relevance
“…The pioneering work by Moaddel and Wainer has established a series of membrane protein chromatographic methods for drug−protein interaction analysis. A systematic study by their group 45,46 and our work 21,22 have shown that K A values by the chromatographic methods are generally lower than those calculated by K d s by radioligand binding assay. In spite of the difference between the two sets of data, the two methods have proved to generate same affinity rank order for diverse ligands.…”
Section: ■ Results and Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…The pioneering work by Moaddel and Wainer has established a series of membrane protein chromatographic methods for drug−protein interaction analysis. A systematic study by their group 45,46 and our work 21,22 have shown that K A values by the chromatographic methods are generally lower than those calculated by K d s by radioligand binding assay. In spite of the difference between the two sets of data, the two methods have proved to generate same affinity rank order for diverse ligands.…”
Section: ■ Results and Discussionmentioning
confidence: 65%
“…Bosentan showed three kinds of sites with various binding affinities. We also determined the association constants of ETA and the four ligands by the other three methods, including traditional frontal analysis, 22 self-competition method, 39 and injection amount-dependent analysis. 39 The binding affinities of these drugs and ETA are within the range of 10 3 to 10 6 M −1 , which are comparable to the previous publications.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous work, Zhao et al. immobilized β 2 ‐adrenoceptor ( β 2 ‐AR), an important drug target for respiratory diseases, onto macroporous silica gel by various immobilization methods [15–18]. The affinity columns were used to screen the bioactive compounds from TCMs, such as Siraitia grosvenorii [19] and Rhodiola crenulate [20].…”
Section: Introductionmentioning
confidence: 99%